2014
DOI: 10.1097/aog.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Identification of iPhone and iPad Applications for Obstetrics and Gynecology Providers

Abstract: Less than 15% of apps found were considered potentially useful to ob-gyns. Thus, the obstetrics and gynecology community is in need of an organized effort to identify, review, and determine the accuracy of apps that can potentially improve the performance of health care providers and lead to better patient outcomes. We propose the formation of a committee to guide in this important task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…Regulatory assemblies, such as the FDA [20], are required to monitor and supervise the process of app publication, marketing and implementation, in order to identify [5], review and determine accuracy and potential health hazards on their use. A recent PLoS One editorial [21] underlined the further limitation of code peer-review, a timely endeavor, and the need for post-publication review.…”
Section: The First Phase: Evaluation and Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory assemblies, such as the FDA [20], are required to monitor and supervise the process of app publication, marketing and implementation, in order to identify [5], review and determine accuracy and potential health hazards on their use. A recent PLoS One editorial [21] underlined the further limitation of code peer-review, a timely endeavor, and the need for post-publication review.…”
Section: The First Phase: Evaluation and Appraisalmentioning
confidence: 99%
“…We have come to an era where health information is readily available. Smartphone utilities demonstrate rapid advancement and the market offers applications (apps) covering almost every aspect of human life, accessible anywhere and anytime; these have engaged practitioners, providing handy tools for information access, monitoring, telemedicine and even supporting medical decisions [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, as mentioned earlier, there is a scarcity of studies regarding communication within emergent fields like obstetrics, and in particular a gap regarding textmessaging-based communications. 20 There are limitations inherent in this study. First, this study measures perceived change rather than objective change.…”
Section: Discussionmentioning
confidence: 93%
“…Further, apps may provide inaccurate information [49], have poor functionality [48], be of dubious quality [50,51], and may even encourage harmful behaviours [46]. Two separate studies examining the usefulness of pregnancy apps found that less than six percent (3.3% and 5.5% respectively) were considered potentially useful by health care providers [1,52]. In a US study comparing two nationally endorsed apps [53], less than 20% of content explicitly addressed recommended prenatal care content.…”
Section: Areas For Concern: Regulation and Validity And Reliability mentioning
confidence: 99%
“…As well as calls for the creation of a regulatory framework [2], many researchers have recommended that health professionals and institutions take the initiative to provide both reliable information on maternal health through such mechanisms as apps, and/or advice about the reliability or validity of other available electronic information [2,47,52]. This desire is echoed by patients [19,20].…”
Section: A Need For Expert Reliable Advice From Local Sourcesmentioning
confidence: 99%